The Cost-Benefit Analysis of Fisheries Management Systems in Kenya: The Case of Lake Victoria - Mokua, Millicent A.; Makindi, Stanley Maingi; Esilaba, Moses (My University, 2014)
Fisheries management costs are widely becoming issues used to choose among policy objectives. We provide simple calculations by drawing on the experience from Lake Victoria fisheries. The study applied cost- benefit analysis based on the transaction costs among four systems of individual transferable quotas, taxation, licensing and community-based management. The objective of the study was to identify a feasible policy combination for the management of Lake Victoria fisheries. It was hypothesized that the combination of community-based management and individual transferable quotas provide a feasible management framework for the fishery. The analysis provides evidence that transaction costs are lower in community=based management. The advantages of individual transferable quotas are also considerable. But, it is concluded that although community management is more cost-effective, their potential for the fishery are not obvious given the prevailing socio-economic conditions along the shores of Lake Victoria. The nature of Lake Victoria fishery is also not appropriate for the introduction of individual transferable quotas. Co-management system is therefore recommended.
Keywords: Fisheries resources; Fisheries management; Transaction cost; Cost benefits analysis; Fishermen